2016
DOI: 10.2337/ds16-0036
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Type 1 Diabetes in Children and Adolescents

Abstract: IN BRIEF In children and adolescents with type 1 diabetes, exposure to glycemic extremes (severe hypoglycemia, chronic hyperglycemia, and diabetic ketoacidosis) overlaps with the time period of most active brain and cognitive development, leading to concerns that these children are at risk for cognitive side effects. This article summarizes the existing literature examining the impact of glycemic extremes on cognitive function and brain structure in youth with type 1 diabetes and points out areas for future re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 57 publications
1
37
0
1
Order By: Relevance
“…Finally, we cannot completely exclude the possibility that differences in cognitive ability between diabetic and healthy groups may have partially contributed to the taste recognition findings, since diabetes is known to impair cognition to some extent [71,72]. However, this interpretation should be taken with caution because, at present, evidence regarding the pediatric population is insufficient to support that youth with T1D display cognitive deficits or differences compared to control subjects.…”
Section: Discussionmentioning
confidence: 87%
“…Finally, we cannot completely exclude the possibility that differences in cognitive ability between diabetic and healthy groups may have partially contributed to the taste recognition findings, since diabetes is known to impair cognition to some extent [71,72]. However, this interpretation should be taken with caution because, at present, evidence regarding the pediatric population is insufficient to support that youth with T1D display cognitive deficits or differences compared to control subjects.…”
Section: Discussionmentioning
confidence: 87%
“…This is backed up by previous studies showing a potential effect of chronic hypoglycemia on gray matter volume and posterior cortical regions. 7 Moreover, the coincidence of seizures and hypoglycemia has well known detrimental effects on cognitive performance including attention tasks and verbal/visual memory. 8 In addition, past severe hypoglycemia was described to be associated with poorer performance on verbal and spatial memory tasks after 2 years in children.…”
Section: Discussionmentioning
confidence: 99%
“…Especially during the early ages, severe as well as chronic subclinical hypoclycemia phases might lead to alterations in normal brain and cognitive development. 7,8 As previously described, hypoglycemic episodes are considered to be associated with alterations in overall cognitive functioning as well as verbal and visual memory in children with type 1 diabetes mellitus. 7 Moreover and as a matter of fact, acute severe hypoglycemia accompanied by seizures might increase the-per se high -risk for sudden unexpected death in epilepsy patients especially in patients with DS.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies also showed that the profiles of fasting state appetite regulating hormones including insulin and leptin were different between breast-and formula-fed infants (Breij et al, 2017;Vasquez-Garibay et al, 2019). Moreover, these hormones have associated with brain development and cognitive function (Plagemann et al, 2005;Farr et al, 2015;Cato and Hershey, 2016).…”
Section: The Physical Properties Of Lipids and Lipid Globulesmentioning
confidence: 99%